Hope and pediatric health. (February 2023) - Lancaster, Brittany D.; Van Allen, Jason
Abstract: Snyder's Hope Theory and its application in pediatric health have been receiving increased attention recently. Within the last three years, research has primarily focused on adolescents and/or young adults, and pediatric cancer populations. Generally, higher hope scores are associated with positive outcomes in pediatric studies. There has also been increased interest in the role of hope in pediatric health interventions, with some studies indicating that hope is malleable and that changes in hope are associated with changes in health outcomes. Limitations in this research area include (1) a few longitudinal and follow-up studies assessing the stability of changes in hope, (2) the need to determine directionality regarding hope and health outcome relations, and (3) some inconsistencies in the conceptualization of hope.